ABO Mismatch in Allogeneic Hematopoietic Stem Cell Transplant: Effect on Short- and Long-term Outcomes. Issue 8 (August 2021) - Valentini, Caterina Giovanna; Metafuni, Elisabetta; Gallo, Lorenzo; Giammarco, Sabrina; Orlando, Nicoletta; Bianchi, Maria; Sica, Simona; Bacigalupo, Andrea; Chiusolo, Patrizia; Teofili, Luciana
Abstract : Background: The impact of ABO incompatibility (ABO-I) on hematopoietic stem cell transplant outcomes is still debated. Methods: We retrospectively investigated 432 consecutive transplants performed at our center (2012–2020). All patients but 6 were affected by hematologic malignancies. The effect of different ABO match combinations on engraftment rate, transfusion support, acute and chronic graft-versus-host disease incidences, nonrelapse mortality (NRM), disease-free survival, and overall survival was assessed in univariate and multivariate analysis. Significance was set at P < 0.05. Results: ABO match distribution among transplants was as follows: 223 ABO-compatible, 94 major ABO-I, 82 minor ABO-I, and 33 bidirectional ABO-I. At univariate analysis, major ABO-I delayed the engraftment of neutrophils, platelets, and erythroid cells. At multivariate analysis, major ABO-I transplants displayed delayed erythroid engraftment (odds ratio [OR], 0.51; 95% confidence intervals [CIs], 0.38-0.70; P < 0.0001) and hindered transfusion independence for both red blood cells (OR, 0.52; 95% CI, 0.37-0.72; P = 0.0001) and platelets (0.60; 95% CI, 0.45-0.86; P = 0.0048). Moreover, major ABO-I transplants received greater amounts of blood products ( P < 0.0001 for red blood cells and P = 0.0447 for platelets). In comparison with other ABO matches, major ABO-I was associated with an increased NRM (OR, 1.67; 95% CI, 1.01-2.75; P = 0.0427). No effects of ABO-mismatch were found on graft-versus-host disease, disease-free survival, and overall survival. Conclusions: Major ABO mismatch delays multilineage engraftment hinders transfusion independence and increases NRM. The prognostic impact of transfusion burden in hematopoietic stem cell transplantation deserves to be explored. Abstract : Supplemental Digital Content is available in the text.